Research Progress on Structural Identification and Biological Activity of Chinese Jujube Polysaccharides - ZHANG Tingting, JIA Shan, MA Huan, FENG Bo, WANG Bini, MENG Yonghong, YANG Xingbin, LU Yalong (Shipin Kexue)
Chinese jujube (Ziziphus jujuba Mill.) originated from China and has high nutritional and medicinal value. As one of the major active ingredients in Chinese jujube, polysaccharides have various functions including immunoregulatory, hepatoprotective, anemia-relieving, lipid-lowering, anti-obesity and gut microbiota regulatory effects. On the basis of extraction and purification of Chinese jujube polysaccharide, current research on the structures of Chinese jujube polysaccharides focuses on the modification of primary structures, monosaccharide composition, molecular mass and glycosidic linkages. However, the relationship between the structure and activity of Chinese jujube polysaccharides and the mechanism of action bioactive polysaccharides from Chinese jujube have not been fully determined. This paper reviews the current progress on the structural characterization and biological activity of Chinese jujube polysaccharides in the literature, and gives an outlook on future research. It is expected that this review will provide a theoretical basis for the wide application of Chinese jujube polysaccharides in health foods, medicine and other fields.